2021
DOI: 10.1016/j.hpb.2021.08.057
|View full text |Cite
|
Sign up to set email alerts
|

First Year of the European Registry for Minimally Invasive Pancreatic Surgery (E-MIPS)

Abstract: Purpose: The European registry for minimally invasive pancreatic surgery (E-MIPS) collects data on laparoscopic and robotic MIPS procedures in all low-and high-volume centers across Europe. The aim is to monitor and report on safety and quality outcomes of MIPS in daily clinical practice. Pancreatic surgery is known for high postoperative morbidity rates. The minority of these procedures is done through a minimally invasive approach. Methods: This is an analysis in the prospective multicenter E-MIPS registry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several nationwide and multicenter studies have been published or are still ongoing [32][33][34][35][36]. Sharpe et al found a higher 30-day mortality rate in patients treated laparoscopically (OR 1.89, p = 0.009), using data from the National Cancer Database.…”
Section: Multicenter Studiesmentioning
confidence: 99%
“…Several nationwide and multicenter studies have been published or are still ongoing [32][33][34][35][36]. Sharpe et al found a higher 30-day mortality rate in patients treated laparoscopically (OR 1.89, p = 0.009), using data from the National Cancer Database.…”
Section: Multicenter Studiesmentioning
confidence: 99%